Comparative Assessment of Spot Welding and Lock Seam on Automotive Inner Tubes for QCDSM and Product Lifecycle Sustainability - Nurhadi, Hikari Qurrata'ain; Mustofa, Mustofa; Solih, Edwin Sahrial; Gurning, Ridho Hans (Journal of Mechanical Engineering, Science, and Innovation, 2025)
In the automotive manufacturing industry, enhancing quality and productivity is crucial to meet customer expectations while ensuring safety, environmental sustainability, and energy efficiency. This study evaluates the collapse strength of automotive inner tubes following ISO 2941 standards, comparing lock seam design with SGCC material and resistance spot welding (RSW) applied to SECD material. The findings show that the lock seam process improves structural strength by approximately 20%, due to more uniform pressure distribution, leading to better stability. A key advantage of the lock seam is its spiral construction, which contrasts with RSW's localized spot welds, contributing to more consistent performance. Additionally, the lock seam process reduces production costs and minimizes environmental impact by using thinner, cost-effective SGCC material. It also enables faster production, enhancing delivery efficiency. The absence of welding fumes improves safety conditions and boosts operator morale, while contributing to a cleaner working environment. From a Product Lifecycle Management perspective, this study shows that the lock seam process optimizes design quality, production efficiency, and sustainability, aligning with the goals of Quality, Cost, Delivery, Safety, and Morale (QCDSM). These results support the adoption of lock seam technology for sustainable, efficient automotive manufacturing.